An open‐label, single‐arm, phase 2 trial of the polo‐like kinase inhibitor volasertib (BI 6727) in patients with locally advanced or metastatic urothelial cancer. Issue 7 (11th December 2013) - Stadler, Walter M.; Vaughn, David J.; Sonpavde, Guru; Vogelzang, Nicholas J.; Tagawa, Scott T.; Petrylak, Daniel P.; Rosen, Peter; Lin, Chia‐Chi; Mahoney, John; Modi, Sanjiv; Lee, Peter; Ernstoff, Marc S.; et al.
Abstract : BACKGROUND: Polo‐like kinases (Plks) control multiple steps during the cell cycle, and Plk1 is overexpressed in urothelial cancer (UC). Volasertib (BI 6727), a Plk inhibitor, has demonstrated antitumor activity in several malignancies, including UC. In this phase 2 trial, the authors investigated volasertib as a second‐line treatment in advanced/metastatic UC. METHODS: Patients who progressed within 2 years of 1 prior chemotherapy regimen received 300 mg volasertib on day 1 every 3 weeks. The dose was escalated to 350 mg in cycle 2 if volasertib was tolerated in cycle 1. The primary endpoint was tumor response, which was assessed every 6 weeks; secondary endpoints were progression‐free survival, overall survival, duration of response, safety, and pharmacokinetics. RESULTS: Fifty patients were enrolled, and the median patient age was 68.5 years (range, 52‐83 years). All patients had received prior platinum, 94% of patients had relapsed ≤2 years after prior therapy, 36% had liver metastases, and 54% had lung metastases. The median number of treatment cycles was 2 (range, 1‐27 treatment cycles), and 23 patients were dose escalated at cycle 2. Seven patients (14%) had a partial response, 13 (26%) had stable disease, and 30 (60%) progressed within 6 weeks. The median response duration was 41 weeks (range, 29.1‐77.3 weeks). The median progression‐free survival was 1.4 months, and the median overall survival was 8.5 months. The most frequent grade 3 and 4 adverse events were neutropenia (28%), thrombocytopenia (20%), and anemia (16%). No cumulative toxicity was observed. CONCLUSIONS: Volasertib as second‐line treatment for advanced/metastatic UC had an acceptable safety profile but demonstrated insufficient antitumor activity for further evaluation as a monotherapy. Cancer 2014;120:976–982 . © 2013 American Cancer Society . Abstract : In this open‐label, single‐arm, phase 2 trial of volasertib as a second‐line treatment in patients with advanced or metastatic urothelial cancer, responses are achieved with a manageable safety profile. However, there is insufficient activity for further clinical investigation of volasertib as a single agent in this setting.